Stories of Queer Enchantment: Attuning to Life’s Vibrancy in Service of Joyous Presents and Co-Flourishing Futures - Hale, Marie; Herndlhofer, El (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
This article investigates queer enchantment as a valuable pathway into greater intimacy with entangled human and more-than-human worlds of vibrancy so threatened at this time. The landscape of contemporary research on enchantment, though rich and vast, is missing a queer theorisation, and a weaving with queer lived-experience. Some contemporary research perpetuates harmful colonial binary modes of thought along cis-heteropatriarchal lines, which serve to exclude and reproduce hierarchical and oppressive organisations of worlds. Framed within adrienne maree brown’s 2019 call to pleasure activism - which asks that we include and centre the pleasure of those most marginalised by systems of harm - this research investigates enchantment as a possible life-affirming pathway of (re)connection and enhanced responsibility.Through a decolonial, collaborative, participatory research methodology, this paper centres the stories of twelve queer-identifying participants in the UK and Ireland, seeking to ground theoretical exploration in lived empirical worlds. Centring a range of voices, the paper seeks to address exclusionary definitions of enchantment and co-create formulations that amplify the most meaningful potentials of an enchantment queered – its fundamental multitudes of difference, its affinity for questioning and complexity, its practicing humility and fluidity in the unknown, and its disruption of destructive norms – in service of cultivating new ways of living together in times of multiple intersecting crises.